1996
DOI: 10.1159/000244336
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Modulates Glomerular Filtration and Renal Blood Flow of the Newborn Rabbit

Abstract: The current study was performed in 17 anesthetized and mechanically ventilated newborn rabbits to investigate the role of nitric oxide (NO) in the regulation of basal renal function of the immature kidney. Renal blood flow and glomerular filtration rate were determined by the clearance of p-aminohippuric acid and inulin, respectively. In 9 newborn rabbits (group 1), L-NAME, a NO synthesis inhibitor, significantly increased the renal vascular resistance by 31 ± 9% and decreased the renal blood flow by 20 ± 6%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…In further support of this conjecture, it is well established that the AT 2 R functions via a nitric oxide (NO)-mediated pathway to produce cyclic GMP and increase vasodilatation (20). Certainly, there is abundant evidence in the literature that NO plays a significantly greater role in the maintenance of hemodynamic function in the neonatal vs. adult kidney, including providing protection against the vasoconstrictor effects of AngII in the newborn (21)(22)(23)(24). Furthermore, there are reports that NO production in the renal vasculature is significantly greater in the newborn vs. adult renal vasculature under normal physiological conditions (4).…”
Section: Discussionmentioning
confidence: 97%
“…In further support of this conjecture, it is well established that the AT 2 R functions via a nitric oxide (NO)-mediated pathway to produce cyclic GMP and increase vasodilatation (20). Certainly, there is abundant evidence in the literature that NO plays a significantly greater role in the maintenance of hemodynamic function in the neonatal vs. adult kidney, including providing protection against the vasoconstrictor effects of AngII in the newborn (21)(22)(23)(24). Furthermore, there are reports that NO production in the renal vasculature is significantly greater in the newborn vs. adult renal vasculature under normal physiological conditions (4).…”
Section: Discussionmentioning
confidence: 97%
“…Solhaug et al were the first to show an enhanced role for NO in the neonate in 1993, when intrarenal infusion of the nonspecific NOS inhibitor l-NAME into porcine caused significantly greater changes in RVR, RBF, and GFR in the newborn, than in the adult (6). This finding by Solhaug et al was confirmed in other animal models (lambs and rabbits) in which nonspecific NOS inhibition increased RVR while decreasing RBF and GFR much more significantly in neonates than in adult kidneys (4,5,8). These early studies demonstrated that the renal hemodynamics of the neonate is much more dependent on NO than that of the adult to maintain normal physiological function; however, the characteristics and exact nature of the enhanced role of NO remain unidentified.…”
Section: Discussionmentioning
confidence: 87%
“…Various studies have shown that nitric oxide (NO) plays a much more pronounced role in the neonate's hemodynamic state, as compared with the adult's, and NO counterbalances the highly activated reninangiotensin system (RAS), protecting the immature kidney from the deleterious effects of adverse perinatal events that lead to vasomotor acute renal failure (2)(3)(4)(5)(6)(7). The immature renal vasculature is highly responsive to intrarenal NO stimulation with acetylcholine and NO inhibition with the nonselective nitric oxide synthase (NOS) inhibitor L-nitro-arginine methyl ester (l-NAME) (8)(9)(10)(11), producing significantly greater increases in RVR and decreases in RBF and GFR in the immature kidney, as compared with the adult.…”
mentioning
confidence: 99%
“…Our group previously demonstrated that L-NAME administration was accompanied by a worsening of the hypoxemia-induced renal vasoconstriction, suggesting that endogenous NO is functionally present in the immature kidney and that NOS activity is maintained during acute hypoxemia [6]. Moreover, endogenous NO maintains neonatal basal renal perfusion mainly through postglomerular renal vascular resistance [37].…”
Section: Discussionmentioning
confidence: 98%